Middle Manager Leadership and Frontline Employee Performance: Bypass, Cascading, and Moderating Effects - Yang, Jixia; Zhang, Zhi‐Xue; Tsui, Anne S. (Journal of Management Studies, 2010)
abstract We investigated the relationship between middle managers' transformational leadership and the performance of frontline employees who are two levels below the middle managers. We identified two pathways through which this cross‐level influence occurs and tested two moderators operating on these two pathways. The first pathway is a direct effect from middle managers to employees, bypassing the influence of employees' immediate supervisor (the bypass effect). We further hypothesized that the bypass effect is moderated by the employees' collectivistic value. The second pathway is a cascading of leadership behaviours from middle managers to first‐line supervisors, whose transformational leadership then enhances employees' performance (the cascading effect). We further hypothesized that this cascading effect is moderated by the supervisors' power distance value. These hypotheses were tested with a sample of 491 frontline employees, 98 frontline supervisors, and 30 middle managers in three organizations in China. The three‐level hierarchical linear modelling results supported the four hypotheses.